2021
DOI: 10.1038/s41598-021-88130-w
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of geographic differences in comorbidities and associated severity and mortality among individuals with COVID-19

Abstract: Several comorbidities have been shown to be associated with coronavirus disease 2019 (COVID-19) related severity and mortality. However, considerable variation in the prevalence estimates of comorbidities and their effects on COVID-19 morbidity and mortality have been observed in prior studies. This systematic review and meta-analysis aimed to determine geographical, age, and gender related differences in the prevalence of comorbidities and associated severity and mortality rates among COVID-19 patients. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
210
5
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(249 citation statements)
references
References 55 publications
(40 reference statements)
19
210
5
15
Order By: Relevance
“…Evidence was weakest for hypertension as an independent risk factor for severe outcomes. Two similar reviews that were published whilst our rapid review was under peer reviewand included some more recent studies -found similar results (33,34), although another found no association with obesity in meta-analysis (33)(34)(35).…”
Section: Summary Of Findingsmentioning
confidence: 60%
See 1 more Smart Citation
“…Evidence was weakest for hypertension as an independent risk factor for severe outcomes. Two similar reviews that were published whilst our rapid review was under peer reviewand included some more recent studies -found similar results (33,34), although another found no association with obesity in meta-analysis (33)(34)(35).…”
Section: Summary Of Findingsmentioning
confidence: 60%
“…Furthermore, patients in many studies had not yet reached their clinical endpoint. We now also note that similar reviews were published while ours was under peer review, and are also primarily focused on samples of hospitalised patients [e.g., (33)(34)(35)].…”
Section: Strengths and Limitations Of The Evidence Basementioning
confidence: 96%
“…Die häufigsten Komorbiditäten waren Depression/Angst (42 %) und Autoimmunerkrankungen (16 %). Die häufigsten neurologischen Manifestationen waren Benommenheit (81 %), Kopfschmerzen (68 %), Taubheitsgefühl/Kribbeln (60 %), Dysgeusie (59 %), Anosmie (55 %) und Myalgien (55 %), Schwindel (47 %), Schmerzen (43 %), verschwommenes Sehen (30 %) und Tinnitus (29 %), 85 % litten unter Müdigkeit [ 46 ].…”
Section: Langzeitfolgenunclassified
“…According to a systematic review, the most prevalent associated diseases are hypertension (32%), obesity (25%), diabetes (18%), and cardiovascular disease (16%), whereas COVID-19 patients with chronic kidney or other renal diseases (51%, 44%), cerebrovascular accident (43%, 44%), and cardiovascular disease (44%, 40%) had more severity and mortality respectively. Additionally, substantial variation in the prevalence of comorbidities and associated disease severity and mortality in different geographic regions was observed, with the highest mortality in Latin American and European patients with any medical condition, mostly male older adults ( 9 ).…”
Section: Introductionmentioning
confidence: 99%